2021
DOI: 10.1007/s00339-021-05165-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetic and superhydrophobic nickel nanoparticles by plasma arc discharge method, application for efficient recoverable and repeatable oil separation from oily-water

Abstract: Nowadays, the contamination of water due to oily waste is causing a serious threat to the environment. There is a need of a method that possesses a simple treatment route, low operational cost and high durability. The oil-water extractors, using magnetic-hydrophobic nanoparticles, act as an efficient method to separate the oil present in the waste water. In this study, thermal plasma system was developed which was found to be the effective and eco-friendly method for materials processing such as the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…14 Each of these approaches has unique benefits and drawbacks, and they all result in the production of tiny particles made of pure metals, alloys, oxides, and composite materials. 15,16 Graphitic carbon nitride (g-CN) is a metal-free semiconductor characterized by its layered structure, which is analogous to that of graphene. One of the defining features of g-CN is its high nitrogen content, with a carbon-to-nitrogen ratio of 3:4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Each of these approaches has unique benefits and drawbacks, and they all result in the production of tiny particles made of pure metals, alloys, oxides, and composite materials. 15,16 Graphitic carbon nitride (g-CN) is a metal-free semiconductor characterized by its layered structure, which is analogous to that of graphene. One of the defining features of g-CN is its high nitrogen content, with a carbon-to-nitrogen ratio of 3:4.…”
Section: Introductionmentioning
confidence: 99%
“…It has also gained popularity in military and space research because of its ability to improve thermo-mechanical characteristics. , Direct nitridation and carbothermal reduction nitridation of aluminum sources have all historically been used to synthesize AlN NPs. , However, these methods have several built-in limitations, such as the production of irregularly granulated powders with a wide and uneven distribution of particle sizes, the need for many processing steps, the high gas consumption, and the prolonged reaction periods that lead to subpar yield. , Different plasma processes, including RF plasma, arc plasma spray, and nontransferred arc plasma, have been used to create AlN nanoparticles to get around these restrictions . Each of these approaches has unique benefits and drawbacks, and they all result in the production of tiny particles made of pure metals, alloys, oxides, and composite materials. , …”
Section: Introductionmentioning
confidence: 99%
“…Yugeswaran et al , 37 synthesized zirconium nitride slags from a zirconium-bearing ore (ZrSiO 4 sand) by a transferred arc thermal plasma method involving carbothermic reduction and nitridation processes in a nitrogen atmosphere. Sivakumar et al , 38 reported the preparation of magnetic superhydrophobic metallic nickel nanoparticles by the thermal plasma arc discharge method. They prepared nickel nanoparticles with spherical morphology and soft ferro-magnetic behaviors, which was used for highly durable oil–water separation applications.…”
Section: Introductionmentioning
confidence: 99%